(untitled) - Schnugh, Monique

Integrating grazing cattle into vineyards and its effect on soil fertility and health, cover crop production, and animal production and profitability (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.